Using state level employment thresholds to explain Okun's Law - Ryan W. Herzog (IZA Journal of Labor Policy, 2013)
In this paper we implement a non-dynamic panel threshold model for fifty U.S. states to better understand the factors determining changes in Okun's Law. We test for asymmetries in Okun's Law controlling for changes in industry employment. We find changes in output on unemployment are least sensitive for states with relatively large employment within government, construction, and natural resources sectors and lower employment levels in financial, professional and business services and manufacturing sectors. States with lower manufacturing employment have a less sensitive output to unemployment relationship, but the reverse does not apply. States with larger shares of employment within manufacturing sectors do not have a significantly more sensitive relationship compared to the national average.
Keywords: E3; R1; J6; 330; Okun's Law; United States; Unemployment; Output; Thresholds